2000
DOI: 10.1128/jb.182.5.1352-1355.2000
|View full text |Cite
|
Sign up to set email alerts
|

Respiration of 2,4,6-Trinitrotoluene by Pseudomonas sp. Strain JLR11

Abstract: Under anoxic conditions Pseudomonas sp. strain JLR11 can use 2,4,6-trinitrotoluene (TNT) as the sole N source, releasing nitrite from the aromatic ring and subsequently reducing it to ammonium and incorporating it into C skeletons. This study shows that TNT can also be used as a terminal electron acceptor in respiratory chains under anoxic conditions by Pseudomonas sp. strain JLR11. TNT-dependent proton translocation coupled to the reduction of TNT to aminonitrotoluenes has been observed in TNT-grown cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 25 publications
(18 reference statements)
0
73
0
3
Order By: Relevance
“…Pseudomonads became prevalent in the highly contaminated soil. On multiple occasions pseudomonads have been isolated on the basis of their utilization of TNT as a nitrogen source, and their ability to transform TNT has been observed (30)(31)(32). It has been suggested that the prevalence of reports about pseudomonads transforming TNT in the literature was due to the ease with which this group of bacteria are cultured (33).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonads became prevalent in the highly contaminated soil. On multiple occasions pseudomonads have been isolated on the basis of their utilization of TNT as a nitrogen source, and their ability to transform TNT has been observed (30)(31)(32). It has been suggested that the prevalence of reports about pseudomonads transforming TNT in the literature was due to the ease with which this group of bacteria are cultured (33).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ramos and colleagues described a different mechanism for the anoxic degradation of TNT (68,69). They isolated a facultative Pseudomonas sp., designated strain JLR11, which was able to grow on TNT as the sole nitrogen source with glucose as a cosubstrate.…”
Section: Vol 65 2001 Metabolism Of Nitroaromatic Compounds 341mentioning
confidence: 99%
“…Another pathway has been described in Pseudomonas sp. strain JLR11 and involves nitrite release and further reduction to ammonium, with almost 85% of the nitrogen of TNT incorporated as organic nitrogen in the cells (68,69). In this review we intend to highlight the recent discovery of TNT as an alternative electron acceptor in respiratory chains of a facultative Pseudomonas strain (69).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, these compounds can be used as electron acceptors for respiration with the subsequent reduction and removal of the nitro substituents (108,109). However, some nitrogencontaining xenobiotics are finally channeled to single-aminoaromatic compounds such as anthranilate (2-aminobenzoate).…”
Section: -Aminobenzoate (Anthranilate) Catabolismmentioning
confidence: 99%
“…On the other hand, aromatic compounds can participate in anaerobic metabolism by serving as electron acceptors rather than electron donors, generally with accompanying modifications of ring substituents that do not perturb the benzene nucleus itself (e.g., chlorinated aromatics as electron acceptors in dehalorespiration, reduction of the acrylate side chain of aromatic compounds, and reduction of nitroaromatics, etc.) (45,88,105,108,109,128,160,169,338). As indicated above, different peripheral pathways involved in the anaerobic activation of a wide variety of (monocyclic) aromatic compounds lead to a few central aromatic intermediates, e.g., resorcinol (1,3-dihydroxybenzene), phloroglucinol (1,3,5-trihydroxybenzene), hydroxyhydroquinone (HHQ) (1,2, 4,-trihydroxybenzene), 6-hydroxynicotinate, hydroxybenzoylCoA, methylbenzoyl-CoA, aminobenzoyl-CoA, and benzoylCoA, with the latter being the most common and studied intermediate ( Fig.…”
Section: Introductionmentioning
confidence: 99%